The MFM program: a successful model in the field of food addiction recovery - Gudmundsdottir, Esther Helga; Rynn, Veronique (Frontiers in Public Health, 2025)
This article outlines how one program in Iceland, the MFM program, is helping clients recover from food addiction and ultra-processed food addiction. The MFM program, founded and developed by Esther Helga Gudmundsdottir (EG), arose from her own recovery from food addiction. Seeing the gap in services for clients with food addiction and ultra-processed food addiction, EG set out to develop a treatment plan based on everything she learned over the years and through her experience and trainings.